2014
DOI: 10.1111/jvs.12194
|View full text |Cite
|
Sign up to set email alerts
|

Do groundwater dynamics drive spatial patterns of tree density and diversity in Neotropical savannas?

Abstract: Questions What are the temporal and spatial variations of groundwater depth along topographic gradients in Neotropical savannas? Are patterns of tree density and species diversity along topographic gradients in Neotropical savannas controlled by water table depth? Do soil and groundwater nutrient concentrations differ along topographic gradients in Neotropical savannas? Location Fire‐protected savannas of central Brazil. Methods Over 16 mo, we monitored temporal and spatial variations in groundwater levels usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 32 publications
2
30
1
1
Order By: Relevance
“…Villalobos‐Vega et al . () studied 10 monitoring wells with water table depths ranging from 0.18 to 15.56 m in an undisturbed cerrado and also found little WTFs in regions with deep water tables. They found that these regions tend to exhibit greater tree abundance and diversity than sites with shallow water tables.…”
Section: Resultsmentioning
confidence: 99%
“…Villalobos‐Vega et al . () studied 10 monitoring wells with water table depths ranging from 0.18 to 15.56 m in an undisturbed cerrado and also found little WTFs in regions with deep water tables. They found that these regions tend to exhibit greater tree abundance and diversity than sites with shallow water tables.…”
Section: Resultsmentioning
confidence: 99%
“…This may happen because the flux of water reaching the groundwater zone may be in balance to groundwater outflow (water recharge is equaled the outflow). One of the first studies of groundwater dynamics in the undisturbed cerrado was conducted by Villalobos-Vega et al (2014) from 11 monitored wells with water tables ranging from 0.18 to 15.56 m. The authors found little water table change in regions with deep water tables (up to 15.56 m), and in some wells the recharge water took up to 5 months to reach the groundwater table. They also concluded that the water table depth has a strong influence on variations in tree density and diversity, i.e., regions with deep water tables such as the IAB Figure 5.…”
Section: Cerrado Water Balancementioning
confidence: 99%
“…Also, hydrological fluxes may vary in a typical catchment due to influences of topographic location (e.g., whether close to a stream or upland, whether in a depression or not), which affect soil water contents. Villalobos-Vega et al (2014) concluded that water table depth has a strong influence on variations in tree density and diversity, i.e., regions with deep water tables such as the IAB site (35 m) tend to exhibit greater tree abundance and diversity than sites with a shallow water table. Therefore, if there is variation in the vegetation characteristics we can expect changes in the hydrological fluxes on different parts of a catchment.…”
Section: Broader Implications For Hydrological Processes In the Cerramentioning
confidence: 99%
“…), climate (precipitation, temperature, and seasonality), and variations in water table depth ( e.g ., Villalobos‐Vega et al . ). A continental‐scale study in African savannas indicated that woody community structure responds to mean annual precipitation and soil texture, which are modified by the effects of fire, domestic livestock, human population density, and cultivation intensity (Bucini & Hanan ).…”
mentioning
confidence: 97%
“…, Villalobos‐Vega et al . ). Thus, both climate and substrate factors related to resource availability are considered essential determinants of species distributions and structures in such savannas (Cole , Solbrig , Campo‐Bescós et al .…”
mentioning
confidence: 97%